PENERTIBAN DAN PENDAYAGUNAAN TANAH TERLANTAR DALAM RANGKA PENATAGUNAAN TANAH DI KOTA TARAKAN - Cariono Cariono (Universitas Borneo Tarakan, 2019)
Abstract The presence of land controlled and / or owned by either existing rights above the ground and based on the new land acquisition in some places there are still many in limbo. Seeing the reality of the field on the wastelands, he made government regulation and government last issued Government Regulation No. 11 Year 2010 on Land Reform and Control of Neglected. Based on this background, the problem is formulated, what basic criteria for establishing a right to the top of the ground as the object of regulating the wastelands, who preferred to get right to the land above the ground of the former wastelands, this research was normative approach legislation conceptual and legal materials. The results showed that the controlling authority is the authority wastelands legacy which the Government (President) delegate to the National Land Agency of the Republic of Indonesia. The mechanism through penertibannya stages: (1) an inventory of land rights or land tenure policies that indicated displaced (2) identification and study of land indicated displaced (3) warning against the rights holder (4) Determination of wastelands. Other Issues Regarding legal protection against former titleholders.Keywords: effectiveness, enforcement, wastelands